Pengaruh Job Demands, Personal Resources, dan Burnout terhadap Work Engagment pada PT. Sanwa Antar Nusa Surabaya - Rahayu, Maria Noventa Asti; Partina, Anna (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This research aims to analyze the influence of job demands, personal resources, and burnout on work engagement at PT. Sanwa Between Nusa Surabaya. Saturated sampling technique was used with a total of 72 respondents. All samples in this study were employees of PT. Sanwa Antar Nusa Surabaya who has the status of a permanent employee. Multiple linear regression analysis was used in this research by first carrying out instrument tests in the form of validity and reliability tests, normality tests, classical assumption tests which include multicollinearity tests and heteroscedasticity tests as well as F (Goodness of Fit) tests, t tests and coefficient of determination. Through these various tests, the results obtained were that the variable job demands (X1) had a negative and significant effect on work engagement, personal resources (X2) had a positive and significant effect on work engagement, and burnout (X3) had a positive and significant effect on work engagement. The results of the research can be a reference for future research related to the variables studied and become a basis for consideration for companies to maintain work engagement among employees.Â